Frequency of Depression in Patients With Diabetes Mellitus Presenting to DHQ Kohat - Ullah, Syed Atta; Mumtaz, Arif; Jalil Khan, Abdul; Khan, Ismail; Ali, Wajid; Khan, Muhammad Hassam (Biological and Clinical Sciences Research Journal, 2025)
Depression is a common but underrecognized comorbidity in patients with diabetes mellitus and adversely affects glycemic control, treatment adherence, and overall quality of life. Objective: To determine the frequency of depression in patients with diabetes mellitus presenting to DHQ Kohat. Methods: This study was conducted in 213 diabetic patients aged 18 to 75 years with HBA1c> 6.5%. The frequency of depression in these diabetic patients was determined. Depression was diagnosed using the PHQ-9 tool and DSM-IV. SPSS 27 was used for analysing the data. Depression was stratified by various demographic and comorbidities using the chi-square test, with a P-value set at ≤ 0.05. Results: The mean age of the patients was 44.62 ± 16.45 years. There were 133 (62.4%) male and 80 (37.6%) female patients. The frequency of depression was 37.6% (n = 80). Depression was significantly associated with female gender, lower economic background, poor glycemic control, hypertension and prolonged diabetes duration. Conclusion: The frequency of depression in patients with diabetes mellitus in our study was 37.6%, and it was notably associated with female gender, lower economic background, poor glycemic control, hypertension and prolonged diabetes duration.